Embedded System to Prevent Traffic Congestion by Creating Traffic Light Delays - Nisarga G. C; Sheethal R; Yashodamma S; Sudha T (Journal of Electronic Design Engineering, 2016)
Increase of vehicles has been created traffic congestion and traffic jams which is a serious threat for the ambulance to reach its destinations in time. We as engineers have to consider this serious problem and duty to make an easy go for the ambulance during emergency. In a solution to solve this threat to prevent further threat to lives we are going to systemize the sensors which optimizes the traffic light operated by microcontroller which is powered by solar panel. This system reduces the traffic jam and congestion up to certain extent. Microcontroller used here is 89S52 which belongs to MCS-51 family. IR Transmitter and Receiver are placed on either side of the road. When vehicle passes in between IR Transmitter and Receiver, IR System is activated. IR System is controlled by microcontroller and t counts the number of vehicle passing on the road and keeps in memory. When vehicle count exceeds the limit microcontroller create the traffic light delays. Based on vehicle count, microcontroller defines different ranges for traffic light delays and update accordingly. At user pre-defined recording interval it records the vehicle count on a real time base. This recorded data is used to analyze traffic conditions in future. This data could be downloaded through communication between the microcontroller and the computer which is done by the computer administrator (access the traffic condition) on a central computer station access the traffic condition and reduce the congestion by creating traffic light delays.